2019
DOI: 10.1038/s41598-019-50466-9
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Marcus Electron and Proton Transfer in Heme Peroxidase Compound II-Catalysed Oxidation Revealed by Arrhenius Plots

Abstract: Electron and proton transfer reactions in enzymes are enigmatic and have attracted a great deal of theoretical, experimental, and practical attention. The oxidoreductases provide model systems for testing theoretical predictions, applying experimental techniques to gain insight into catalytic mechanisms, and creating industrially important bio(electro)conversion processes. Most previous and ongoing research on enzymatic electron transfer has exploited a theoretically and practically sound but limited approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…ABTS oxidation results showed that these Pep-9/hemin nanotubes exhibited a significant decrease in catalytic activity. Compared with Pep-1 , we reasoned that Pep-9 with six Noe groups is unable to facilitate the proton transfer and thus leads to reduced efficiency in oxidation reaction 11 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…ABTS oxidation results showed that these Pep-9/hemin nanotubes exhibited a significant decrease in catalytic activity. Compared with Pep-1 , we reasoned that Pep-9 with six Noe groups is unable to facilitate the proton transfer and thus leads to reduced efficiency in oxidation reaction 11 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we selected horseradish peroxidase (HRP), for which comprehensive data on the reactivity of the enzyme with hydrogen peroxide ( k cat / K M ∼ 10 7 M −1 s −1 ), leucothionine (4.8 × 10 8 M −1 s −1 ), and other substrates are available. 37 In contrast to laccase-based mediator regeneration schemes, the proposed method uses hydrogen peroxide as a terminal electron acceptor instead of oxygen. H 2 O 2 is regarded as a “green” oxidizer in various biocatalytic processes.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, ET rates are estimated for ET from PSII to PSI through chains comprising plastoquinone (PQ), cytochrome b 6 f (Cyt b 6 f ), and plastocyanin (PC). Additionally, Moser et al rigorously investigated tunneling dynamics in PSII . Recently, the Marcus theory has been widely used, e.g., in molecular design for organic semiconductors, proton-coupled ET, and extracellular ET. …”
Section: Introductionmentioning
confidence: 99%